All-solid-state battery preparation method, preparation equipment and all-solid-state battery
By simultaneously applying adhesive and stacking the cells during the stacking process of all-solid-state batteries, the adhesive layer is formed to completely adhere to the empty area on the positive electrode side, thus solving the battery safety and cycle performance problems caused by lithium plating at the edge of the negative electrode and improving the safety and stability of the battery.
Patent Information
- Application Number
- CN202511814221.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-04
- Publication Date
- 2026-03-17
AI Technical Summary
In the process of preparing all-solid-state batteries, lithium dendrites are formed at the edge of the negative electrode, which leads to the deterioration of battery safety and cycle performance. Existing solutions are complex and have poor adaptability.
By simultaneously applying adhesive and stacking the electrodes during the lamination process, the adhesive layer is made to fully adhere to the positive electrode side void, precisely filling the overhang area and preventing the solid electrolyte layer from breaking due to uneven stress. Photocuring and other methods are used to improve the adhesion and stability between the adhesive layer and the electrode.
It improves battery safety and cycle stability, simplifies the production process, enhances the compatibility of the adhesive layer with electrodes of different sizes, and strengthens interlayer interface stability.
Smart Images

Figure CN121688154A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of batteries, in particular to a full-solid battery preparation method, a preparation device and a full-solid battery. BACKGROUND
[0002] In order to avoid the formation of lithium dendrites by lithium precipitation at the edge of the negative electrode, which not only consumes lithium ions but also easily causes short circuit of the battery, in the current production, an overhang area is usually reserved at the edge of the negative electrode tab in the design of the negative electrode area being larger than the positive electrode, which causes the formation of an empty area at the corresponding position of the positive electrode side. In addition, in the preparation process of the full-solid battery, in order to improve the contact, compression is inevitably performed. During compression, the solid electrolyte layer is prone to breakage, resulting in deterioration of the safety performance and cycle performance of the battery. In view of this problem, the existing solution is to set an insulating support at the edge of the positive electrode tab, but this method needs to prepare a rubber frame in advance, and the process is complex and has poor adaptability. SUMMARY
[0003] In order to solve the above problems, the present application discloses a full-solid battery preparation method, a preparation device and a full-solid battery. By improving the lamination gluing process, the gluing process and the lamination process are performed synchronously, the formed rubber layer can completely match the size and shape of the overhang area, and the positive electrode side empty area is accurately filled. This can avoid the breakage of the solid electrolyte layer caused by uneven stress during compaction, effectively guarantee the structural integrity of the electrolyte layer, and further improve the safety performance and cycle stability of the battery.
[0004] The first aspect of the present application provides a full-solid battery preparation method, comprising the following steps:
[0005] S1: Lamination: transferring the composite tab to the operation platform, placing the positive electrode tab above the composite tab to form a lamination structure; wherein the composite tab comprises a negative electrode tab and a solid electrolyte layer arranged on the two side surfaces of the negative electrode tab;
[0006] S2: First gluing: gluing the tab area of the positive electrode tab to form a first rubber layer;
[0007] S3, Second gluing: starting from the edge of the tab of the positive electrode tab, gluing on the solid electrolyte layer along the edge of the positive electrode tab, and then solidifying to form a second rubber layer, thereby preparing an intermediate structure;
[0008] S4, Lamination again: continuing to stack the composite tab and the positive electrode tab on the intermediate structure;
[0009] Repeat steps S2-S4 until the preset number of layers is reached to prepare a full-solid battery.
[0010] In an embodiment, step S1 further comprises pre-pressing the lamination structure.
[0011] In one embodiment, step S1 further includes edge alignment detection of the stacked structure using a detection device.
[0012] In one embodiment, step S1 further includes using a pressure plate to fix the active material layer region of the positive electrode sheet.
[0013] In one embodiment, in step S3, the curing method is photocuring.
[0014] In one embodiment, the preparation method further includes die-cutting the edges of the intermediate structure.
[0015] In one embodiment, the preparation method further includes combining the negative electrode sheet with a solid electrolyte layer to prepare a composite electrode sheet.
[0016] A second aspect of this application provides an apparatus for fabricating an all-solid-state battery, used to implement the above-described fabrication method.
[0017] In one embodiment, the fabrication apparatus includes an operating platform, a transfer module, and a coating module. The transfer module includes a positive electrode transfer mechanism and a composite electrode transfer mechanism.
[0018] A third aspect of this application provides an all-solid-state battery, prepared by the preparation method described in the first aspect or by the apparatus described in the second aspect.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] By improving the lamination coating process, the coating process is carried out simultaneously with the lamination process. The resulting adhesive layer can perfectly fit the size and shape of the overhang area and accurately fill the void area on the positive electrode side. During the lamination process, the positive electrode tab and the surrounding area are coated and cured in stages, which effectively enhances the stability of the interlayer interface. This can fundamentally avoid the problem of solid electrolyte layer breakage due to uneven stress during compression, effectively ensure the structural integrity of the electrolyte layer, and thus improve the safety performance and cycle stability of the battery.
[0021] Moreover, the absence of a pre-prepared adhesive frame effectively improves production efficiency and enhances the compatibility of the adhesive layer with positive electrode sheets and composite electrode sheets of different sizes.
[0022] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the other objects, features and advantages of this application more obvious and understandable, specific embodiments of this application are given below. Attached Figure Description
[0023] Figure 1This is a schematic flowchart of the all-solid-state battery fabrication method in some embodiments of this application;
[0024] Figure 2 This is a schematic diagram of the stacking of all-solid-state battery intermediates in some embodiments of this application;
[0025] Figure 3 This is a top view of an all-solid-state battery intermediate in some embodiments of this application;
[0026] Figure 4 This is a schematic diagram of the structure of an all-solid-state battery fabrication apparatus in some embodiments of this application.
[0027] Explanation of reference numerals in the attached figures:
[0028] 1-Solid electrolyte layer;
[0029] 21-Positive electrode active material layer; 22-Positive electrode current collector; 23-Positive electrode tab;
[0030] 31-Negative electrode active material layer; 32-Negative electrode current collector;
[0031] 41 - First adhesive layer; 42 - Second adhesive layer;
[0032] 100 - Transfer module; 200 - Glue application module; 300 - Operating platform. Detailed Implementation
[0033] Reference will now be made to embodiments of this application in detail with reference to the accompanying drawings, one or more of which are described below. Each embodiment is provided as an explanation and not as a limitation of this application. In fact, it will be apparent to those skilled in the art that various modifications and variations can be made to this application without departing from the scope or spirit of this application. For example, features described or illustrated as part of one embodiment may be used in another embodiment to produce further embodiments.
[0034] Therefore, this application is intended to cover such modifications and variations falling within the scope of the appended claims and their equivalents. Other objects, features, and aspects of this application are disclosed in or will be apparent from the following detailed description. It will be understood by those skilled in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of this application.
[0035] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0036] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0037] In this article, when referring to units of data ranges, if a unit is only followed by the right endpoint, it means that the units of the left and right endpoints are the same.
[0038] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0039] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0040] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0041] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0042] Liquid lithium-ion batteries are now widely used in consumer electronics such as mobile phones, computers and home appliances, transportation such as automobiles and two-wheeled vehicles, and energy storage such as wind and solar power plants. However, there is still room for improvement in the energy density and safety of liquid lithium-ion batteries, prompting the industry to focus on solid-state batteries with higher energy density and greater safety while continuing to develop existing technologies.
[0043] However, after eliminating or reducing the use of electrolyte, in order to ensure good lithium-ion contact inside the battery, the contact requirements between the positive and negative electrodes and the solid electrolyte layer are better. Therefore, it is necessary to perform isostatic pressing on the stacked batteries.
[0044] Meanwhile, in addition to transport between electrodes, lithium ions migrate towards the negative electrode side due to factors such as concentration diffusion, leading to lithium plating and lithium dendrite formation at the negative electrode edge. Therefore, the negative electrode is larger than the positive electrode in both length and width, and the excess area of the negative electrode is called the overhang region. The solid electrolyte layer, which acts as a barrier between the positive and negative electrodes, is generally set to be greater than or equal to the negative electrode. Unlike the positive and negative electrodes, including the current collector, which have a certain degree of toughness, the solid electrolyte layer contains little or no binder. In addition, it is mostly composed of inorganic solid electrolytes, resulting in poor toughness. During isostatic pressing, it is prone to bending and breakage, which increases the internal resistance of the battery and may even cause a short circuit.
[0045] Therefore, this application solves the above problems by forming a gel layer on the solid electrolyte layer circumferentially along the edge of the positive electrode sheet to support the solid electrolyte layer.
[0046] like Figure 1 As shown, in a first aspect, this application provides a method for preparing an all-solid-state battery, comprising the following steps:
[0047] S1: Stacking: Transfer the composite electrode to the operating platform 300, and place the positive electrode on top of the composite electrode to form a stacked structure; wherein, the composite electrode includes a negative electrode and a solid electrolyte layer 1 disposed on both sides of the negative electrode;
[0048] S2: First coating: Apply adhesive to the tab area 23 of the positive electrode sheet to form the first adhesive layer 41;
[0049] S3. Second coating: Starting from the edge of the tab 23 of the positive electrode sheet, the adhesive is applied to the solid electrolyte layer 1 along the edge of the positive electrode sheet, and then cured to form the second adhesive layer 42, thus preparing the intermediate structure.
[0050] S4. Stacking again: Continue to stack composite electrodes and positive electrodes on the intermediate structure;
[0051] Repeat steps S2 to S4 until the preset number of layers is reached to prepare an all-solid-state battery.
[0052] By improving the lamination coating process, the coating process is carried out simultaneously with the lamination process. The resulting adhesive layer can perfectly fit the size and shape of the overhang area and accurately fill the void area on the positive electrode side. During the lamination process, the positive electrode tab and the surrounding area are coated and cured in stages, which effectively enhances the stability of the interlayer interface. This can fundamentally avoid the problem of solid electrolyte layer breakage due to uneven stress during compression, effectively ensure the structural integrity of the electrolyte layer, and thus improve the safety performance and cycle stability of the battery.
[0053] Moreover, the absence of a pre-prepared adhesive frame effectively improves production efficiency and enhances the compatibility of the adhesive layer with positive electrode sheets and composite electrode sheets of different sizes.
[0054] In some embodiments, step S1 further includes pre-compressing the laminated structure.
[0055] Pre-pressing initially fixes the composite electrode and the positive electrode, preventing slippage between them during adhesive coating, which would reduce coating accuracy and prevent adhesive from seeping into the solid electrolyte layer and the positive electrode, contaminating the active area and blocking lithium-ion transport channels. Pre-pressing also makes the edges of the positive electrode neat and regular, which is beneficial for both adhesive coating and CCD positioning. Furthermore, pre-pressing eliminates gaps between the positive electrode, the solid electrolyte layer, and the negative electrode, achieving tight contact between the positive electrode and the solid electrolyte layer 1, and between the negative electrode and the solid electrolyte layer 1.
[0056] Understandably, the pre-pressurization process parameters can be selected based on the specific type of solid electrolyte.
[0057] In some implementations, the pre-compression pressure is 80 MPa to 500 MPa.
[0058] In some implementations, the pre-compression time is 1 min to 30 min.
[0059] In some implementations, the pre-compression temperature is 80°C to 150°C.
[0060] In some embodiments, step S1 further includes edge alignment detection of the stacked structure using a detection device. Exemplarily, the detection device can be a CCD (charge-coupled device) detection device.
[0061] In some embodiments, step S1 further includes using a pressure plate to fix the active material layer region of the positive electrode sheet.
[0062] The pressure plate serves two purposes: firstly, it prevents the stacked wafers from shifting, which would reduce the accuracy of the adhesive application; secondly, it blocks the adhesive from overflowing onto the positive electrode surface.
[0063] In some embodiments, in step S2, after the tab region 23 of the positive electrode sheet is coated with adhesive, it is cured.
[0064] In some embodiments, in step S3, the curing method is photocuring, thermal curing, or self-curing.
[0065] In some preferred embodiments, in step S3, the curing method is photocuring. Photocuring has a fast curing rate, which prevents the curing time from being too long and the adhesive from reacting with the solid electrolyte layer or the positive electrode coating. It can also improve production efficiency. Moreover, photocuring is a low-temperature process, and the reaction is carried out at room temperature. It can be adapted to most solid electrolytes and prevent the solid electrolyte from decomposing when heated, which would lead to the degradation of the battery's cycle performance.
[0066] In some implementations, the photocuring time is 10s to 60s. For example, it can be 10s, 20s, 30s, 40s, 50s, or 60s.
[0067] In some embodiments, in steps S2 and S3, the adhesive liquid used for applying the adhesive includes an adhesive material, which includes one or more of epoxy acrylate, polyurethane acrylate, polyester acrylate, polyvinylidene fluoride, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylic acid, sodium polyacrylate, polyethylene oxide, and polyvinyl alcohol.
[0068] In some preferred embodiments, the adhesive material includes one of epoxy acrylate, polyurethane acrylate, and polyester acrylate.
[0069] In some embodiments, the adhesive solution used for coating may further include ceramic materials, including AT9, AT11 ceramics (a high-performance ceramic material composed of aluminum, titanium, oxygen and nitrogen), alumina, magnesium oxide, titanium oxide and boehmite.
[0070] In some embodiments, the adhesive solution used for coating may also include a solid electrolyte material.
[0071] In some embodiments, the viscosity of the adhesive solution used for coating is 500 mPa·s to 10000 mPa·s.
[0072] In some embodiments, step S3 further includes morphological inspection of the formed adhesive layer after applying the adhesive.
[0073] In some embodiments, the above preparation method further includes die-cutting the edges of the stack composed of the composite electrode and the positive electrode to ensure the flatness of the stack edges.
[0074] In some embodiments, the above preparation method further includes isostatic pressing of the all-solid-state battery.
[0075] In some embodiments, the isostatic pressing temperature is 20–80°C. For example, it can be 20°C, 25°C, 30°C, 40°C, 50°C, 60°C, 70°C, or 80°C.
[0076] In some implementations, the isostatic pressure is 200 MPa to 500 MPa. For example, it can be 200 MPa, 250 MPa, 300 MPa, 350 MPa, 400 MPa, 450 MPa, or 500 MPa.
[0077] In some implementations, the isostatic pressing time is 1 to 10 minutes. For example, it can be 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, or 10 minutes.
[0078] In some embodiments, step S1 further includes bonding the negative electrode sheet to the solid electrolyte layer 1. The bonding method can be pressing, including roll pressing or flat pressing.
[0079] In some embodiments, the pressure of the roller is 10t to 30t, for example, it can be 10t, 12t, 15t, 18t, 20t, 23t, 25t, 28t or 30t.
[0080] In some embodiments, the preparation method further includes the preparation of a positive electrode sheet, the preparation of a negative electrode sheet, and the preparation of a solid electrolyte layer. The preparation of the negative electrode sheet and the preparation of the solid electrolyte layer 1 are applicable to any conventional preparation method in the art.
[0081] like Figure 4 As shown, in a second aspect, this application provides a preparation apparatus for implementing the above-described method.
[0082] In some embodiments, the preparation apparatus includes an operating platform 300, a transfer module 100, and a coating module 200. The transfer module 100 includes a positive electrode transfer mechanism and a composite electrode transfer mechanism (not shown in the figure) for transporting the positive electrode and the composite electrode; the coating module 200 is configured to form a first adhesive layer 41 and a second adhesive layer 42 on and around the tab 23 of the positive electrode.
[0083] In some embodiments, the operating platform 300 is configured to place composite electrode sheets and positive electrode sheets for stacking and coating. The operating platform 300 includes a hollow cavity and a surface including a plurality of vacuum adsorption holes for adsorbing the electrode sheets and preventing misalignment of the positive electrode sheet and composite electrode sheet during pre-pressing.
[0084] In some embodiments, the transfer module 100 includes a positive electrode transfer mechanism and a composite electrode transfer mechanism (not shown in the figure) for conveying the positive electrode and the composite electrode.
[0085] In some embodiments, the positive electrode transfer mechanism includes an electrode cassette, a first driving structure, and a gripping structure. The first driving structure drives the gripping structure to grip the electrode and transfer it from the electrode cassette to the operating platform 300.
[0086] In some embodiments, the electrode cassette is provided with a positioning structure to achieve precise positioning of the electrode by the adsorption structure, preventing the electrode from shifting position after it is transferred to the operating platform 300.
[0087] In some embodiments, the first drive structure includes a servo motor.
[0088] In some embodiments, the gripping structure includes a flat plate structure, which includes a vacuum adsorption element that transfers the electrode by adsorbing the electrode.
[0089] In some embodiments, the composite electrode transfer mechanism has the same structure as the positive electrode transfer mechanism.
[0090] In some embodiments, the glue application module 200 includes a glue application mechanism and a testing mechanism.
[0091] In some embodiments, the adhesive application mechanism includes a pre-compression structure, an adhesive application structure, and a curing structure.
[0092] In some embodiments, the pre-pressing mechanism includes a pre-pressing block and a second driving structure. The second driving structure drives the pre-pressing block to press down, and the second driving structure includes a cylinder or a servo motor. Pre-pressing the stacked composite electrode and positive electrode by the pre-pressing mechanism helps to improve the accuracy of the adhesive coating and prevents the adhesive from entering between the positive electrode and the composite electrode.
[0093] In some embodiments, the adhesive coating structure includes an adhesive coating head, which includes an inlet, a cavity, and an outlet. The adhesive enters from the inlet, passes through the cavity, and flows out from the outlet.
[0094] In some embodiments, the fabrication apparatus further includes a pressure plate configured to fix the positive electrode sheet.
[0095] In some embodiments, the pressure plate is a flat plate structure, and its thickness is greater than that of the positive electrode sheet. When the positive electrode sheet is double-coated, the thickness of the pressure plate is greater than the sum of the thicknesses of the positive current collector and the positive active material layers 21 on both sides.
[0096] In some implementations, the projection of the pressure plate onto the positive electrode sheet is equal to the area of the positive electrode sheet, thereby achieving precise adhesive application to the edge of the positive electrode sheet.
[0097] In some embodiments, the curing structure includes a frame structure for achieving adhesive layer curing. The frame structure can avoid the curing process from affecting the positive electrode active material layer 21.
[0098] In some embodiments, a heating plate is embedded in the surface of the frame structure, and the heating plate is electrically connected to a temperature controller to form a thermosetting unit.
[0099] In some implementations, a UV lamp is embedded in the surface of the frame structure for photocuring.
[0100] In some embodiments, the testing institution is a CCD testing institution.
[0101] In some embodiments, the preparation apparatus further includes a control system electrically connected to the transfer module 100 and the adhesive coating module 200, for controlling each module to work collaboratively according to a preset program.
[0102] In the technical solution of this application embodiment, during the stacking and coating process, the composite electrode is first transferred to the operating platform 300 by the composite electrode transfer mechanism, and then the positive electrode is placed on top of the composite electrode by the positive electrode transfer mechanism. The second driving structure drives the pre-pressing block to press down for pre-pressing. After pre-pressing, the edge morphology is detected by the detection structure. The positive electrode and composite electrode are fixed by the pressure plate. Then, the coating structure performs the first and second coatings. The pressure plate is retracted, and the curing structure cures the adhesive layer. After the detection mechanism detects the morphology and size of the adhesive layer, the composite electrode is stacked onto the coated positive electrode by the composite electrode transfer mechanism. The above operations are repeated to stack the positive electrode, coat the adhesive, etc., to prepare an all-solid-state battery. The adhesive layer is directly formed on the solid electrolyte layer. On the one hand, this prevents the solid electrolyte layer from being crushed during isostatic pressing. On the other hand, it improves the structural stability of the stacked battery.
[0103] like Figures 2-3 As shown, in a third aspect, this application also provides an all-solid-state battery, prepared by the preparation method described in the first aspect or by the apparatus described in the second aspect.
[0104] In some embodiments, the all-solid-state battery includes a positive electrode, a negative electrode, and a solid electrolyte layer disposed on the negative electrode. The positive electrode includes a positive electrode tab, a first adhesive layer is disposed on the positive electrode tab, and a second adhesive layer is disposed on the surface of the solid electrolyte layer, and the second adhesive layer is disposed around the circumferential edge of the positive electrode.
[0105] In some embodiments, the second adhesive layer is disposed in contact with the positive electrode active material layer 21 but does not overlap with it.
[0106] In some embodiments, the thickness of the second adhesive layer is greater than or equal to the thickness of the positive electrode sheet.
[0107] In some embodiments, when the thickness of the second adhesive layer is greater than the thickness of the positive electrode sheet, the difference is less than 1 μm. This arrangement allows for adaptation to volume changes in the positive electrode active material layer 21.
[0108] In some embodiments, the thickness of the first adhesive layer is greater than the thickness of the second adhesive layer, which can effectively prevent electrode breakage.
[0109] In some embodiments, the second adhesive layer covers the area of the solid electrolyte layer that extends beyond the positive electrode active material layer 21. This ensures that the capacity of the all-solid-state battery is not affected, and also prevents the solid electrolyte layer and the negative electrode active material layer 31 from chipping.
[0110] In some embodiments, the positive electrode includes a positive current collector 22 and a positive active material layer 21 disposed on the positive current collector 22.
[0111] In some preferred embodiments, the positive electrode active material layer 21 is disposed on both sides of the positive electrode current collector 22.
[0112] In some embodiments, the positive electrode active material layer 21 includes a positive electrode active material, which includes a compound that can reversibly insert and deintercalate lithium ions.
[0113] In some embodiments, the positive electrode active material comprises one or more transition metal cations, such as manganese (Mn), nickel (Ni), cobalt (Co), chromium (Cr), iron (Fe), vanadium (V), and combinations thereof.
[0114] In some embodiments, the positive electrode active material is one of layered oxides, spinel, and polyanionic materials. For example, layered oxides (e.g., rock salt layered oxides) comprise one or more lithium-based positive electrode active materials selected from: LiCoO2 (LCO), LiNi x Mn y Co 1-x-y O2 (where 0 ≤ x ≤ 1 and 0 ≤ y ≤ 1), LiNi 1-x-y Co x Al y O2 (where 0 ≤ x ≤ 1 and 0 ≤ y ≤ 1), LiNi x Mn 1-x O2 (where 0 ≤ x ≤ 1), and Li 1+x MO2 (where M is one of Mn, Ni, Co, and Al and 0 ≤ x ≤ 1). Spinel contains one or more lithium-based cathode active materials selected from the following: LiMn2O4 (LMO) and LiNi. x Mn 1.5 O4. The olivine type contains one or more lithium-based positive electrode active materials, LiMPO4 (where M is at least one of Fe, Ni, Co, and Mn). The polyanionic cation contains, for example, phosphates such as LiV2(PO4). 24 And / or silicates such as LiFeSiO4.
[0115] In some embodiments, the mass of the positive electrode active material accounts for 60% to 95% of the mass of the positive electrode active material layer 21.
[0116] In some embodiments, the positive electrode active material layer 21 includes a binder. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material layer 21 and the positive electrode current collector 22.
[0117] In some embodiments, non-limiting examples of adhesives include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.
[0118] In some embodiments, the mass of the binder accounts for 0.1% to 20% of the mass of the positive electrode active material layer 21.
[0119] In some embodiments, the positive electrode active material layer 21 includes a conductive agent, thereby imparting conductivity to the electrode. The conductive agent may include any conductive material, as long as it does not cause a chemical change. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, synthetic graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives), and mixtures thereof.
[0120] In some embodiments, the mass of the conductive agent accounts for 0.1% to 20% of the mass of the positive electrode active material layer 21.
[0121] In some embodiments, the positive electrode active material layer 21 provided in this application further includes a fast ion conductor to improve the ionic conductivity of the positive electrode active material layer 21. This application does not limit the type of fast ion conductor, which can be an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a lithium salt, etc.
[0122] In some embodiments, the mass of the fast ion conductor accounts for 1%-20% of the mass of the positive electrode active material layer 21; preferably 5%-20%.
[0123] In some embodiments, the positive current collector 22 comprises a metallic material capable of conducting electrons. For example, the positive current collector 22 comprises at least one of Al, Ni, tin, copper, and stainless steel.
[0124] In some embodiments, the surface of the aluminum foil may be anodized to form a nanoscale aluminum oxide layer, thereby enhancing its corrosion resistance and interfacial bonding with the cathode material.
[0125] In some embodiments, the aluminum alloy foil may contain trace amounts of titanium (Ti) or (Si) to enhance mechanical strength and high-temperature stability.
[0126] In some embodiments, the aluminum foil may also be a carbon-coated aluminum foil.
[0127] In some embodiments, the negative electrode can be an anode-free lithium metal solid-state battery, and the negative electrode can be made of Ag-C alloy and coated on a copper foil serving as the negative electrode current collector 32 to form a negative electrode sheet.
[0128] In some embodiments, the negative electrode sheet includes a negative current collector 32 and a negative active material layer 31 disposed on the negative current collector 32.
[0129] In some embodiments, the negative electrode current collector 32 includes, but is not limited to, any one of copper, nickel, or stainless steel; for example, the negative electrode current collector 32 is copper foil.
[0130] In some embodiments, the shape of the negative electrode current collector 32 includes, but is not limited to, metal foil, metal grid, metal mesh, etc.
[0131] In some embodiments, the negative electrode active material is a compound that reversibly inserts and de-intercalates lithium. The negative electrode active material in this application can be any negative electrode active material known in the art. For example, the negative electrode active material can be selected from at least one of natural graphite, artificial graphite, hard carbon, soft carbon, silicon-based materials, titanium-based materials, tin-based materials, or metallic lithium.
[0132] In some embodiments, the positive electrode and the negative electrode may use the same conductive agent or different conductive agents.
[0133] In some embodiments, the conductive agent in the negative electrode sheet includes, but is not limited to, at least one of carbon-based materials, powdered nickel or other metal particles, or conductive polymers. Examples include natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, acetylene black, carbon nanotubes, carbon nanofibers, polyaniline, polythiophene, polyacetylene, polypyrrole, or poly(3,4-ethylenedioxythiophene)polysulfonated styrene.
[0134] In some embodiments, the negative electrode binder can bond and retain the active material, enhance the contact between the active material and the conductive agent, and between the active material and the current collector, thereby stabilizing the electrode structure.
[0135] In some embodiments, the binder in the negative electrode sheet includes, but is not limited to, thermoplastic resins or thermosetting resins. Examples include polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene-ethylene-butene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, and lithium alginate.
[0136] In some embodiments, the solid electrolyte layer 1 includes solid electrolyte particles. Exemplarily, the solid electrolyte can be an inorganic solid electrolyte or a polymer solid electrolyte, wherein the inorganic solid electrolyte includes oxide solid electrolytes, sulfide solid electrolytes, and halide solid electrolytes.
[0137] In some embodiments, the oxide solid electrolyte may comprise one or more garnet ceramics, LISICON-type oxides, NASICON-type oxides, and perovskite-type ceramics. For example, one or more garnet ceramics may be selected from the group consisting of: Li 6.5 La 24 Zr 1.75 Te 0.25 O 12 、Li7La 24 Zr2O 12 Li 6.2 Ga 0.24 La 2.95 Rb 0.05 Zr2O 12 Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 Li 6.25 Al 0.25 La 24 Zr2O 12 Li 6.75 La 24 Zr 1.75 Nb 0.25 O 12 Li 6.75 La 24 Zr 1.75 Nb 0.25 O 12 And combinations thereof. One or more LISICON-type oxides may be selected from the group consisting of: Li 14 Zn(GeO4)4, Li 24+x (P 1-x Si x O4 (where 0 < x < 1), Li 24+x Ge x V 1-x O4 (where 0 < x < 1) and combinations thereof. One or more NASICON-type oxides can be produced from LiMM′(PO4). 24 Defined where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr, and La. For example: in some variants, one or more NASICON-type oxides may be selected from the group consisting of: Li1+x Al x Ge 2-x (PO4) 24 (LAGP) (where 0 ≤ x ≤ 2), Li 1+x Al x Ti 2-x (PO4) 24 (LATP) (where 0 ≤ x ≤ 2), Li 1+x Y x Zr2-x(PO4)24(LYZP) (where 0≤x≤2), Li 1.24 Al 0.24 Ti 1.7 (PO4) 24 LiTi2(PO4) 24 LiGeTi(PO4) 24 LiGe2(PO4) 24 LiHf2(PO4) 24 And combinations thereof. One or more perovskite ceramics may be selected from the group consisting of: Li 24.24 La 0.524 TiO 24 LiSr 1.65 Zr 1.24 Ta 1.7 O9、Li 2x-y Sr 1-x Ta y Zr 1-y O 24 (where x = 0.75y and 0.60 < y < 0.75), Li 24 / 8 Sr 7 / 16 Nb 24 / 4 Zr 1 / 4 O 24 Li 24x La (2 / 24-x) TiO 24 (where 0 < x < 0.25) and combinations thereof. In one variant, one or more oxide-based materials may have a value greater than or equal to about 10. -5 S / cm to less than or equal to approximately 10 -1 Ionic conductivity in S / cm.
[0138] In some embodiments, the sulfide solid electrolyte may include one or more sulfide-based materials selected from the group consisting of: Li2S-P2S5, Li2S-P2S5-MS x (where M is Si, Ge, and Sn and 0 ≤ x ≤ 2), Li 24.4 Si 0.4 P 0.6 S4, Li10 GeP2S 11.7 O 0.24 Li 9.6 P 24 S 12 Li7P 24 S 11 Li9P 24 S9O 24 Li 10.245 Si 1.245 P 1.65 S 12 Li 9.81 Sn 0.81 P 2.19 S 12 Li 10 (Si 0.5 Ge 0.5 P2S 12 Li (Ge 0.5 Sn 0.5 P2S 12 Li 10 GeP2S 12 (LGPS), Li6PS5X (where X is Cl, Br, or I), Li7P2S8I, Li 10.245 Ge 1.245 P 1.65 S 12 Li 24.25 Ge 0.25 P 0.75 S4, Li 10 SnP2S 12 Li 10 SiP2S 12 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.24 (1-x)P₂S₅-xLi₂S (where 0.5 ≤ x ≤ 0.7) and combinations thereof. In one variant, one or more sulfide-based materials may have a content greater than or equal to about 10 -7 Ionic conductivity from S / cm to less than or equal to about 1 S / cm.
[0139] In some embodiments, the halide solid electrolyte includes Li a M b X c N dM includes one or more of the basic metal elements, such as Zr, Hf, In, Sc, Y, La, Ce, Pr, Nb, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. M also includes doped metal elements, used in conjunction with the aforementioned basic metal elements, such as one or more of Nb, Ta, Al, La, Mg, Ca, Ba, and Ag. X includes one or more of F, Cl, Br, and I. N includes one or more of O and S, and satisfies a + mb = c + nd, where m and n are the weighted valences of M and N, respectively, and 1 ≤ a ≤ 4.
[0140] In some embodiments, the halide solid electrolyte particles may be Li₂ZrCl₆, Li₂ZrCl₅F, or Li₂ZrCl₆. 5.5 O 0.25 At least one of Li3InCl6, Li3YCl6, Li2HfCl6, LiInBr4, Li3InBr6, Li3LaI6, Li3LuCl6, and Li3ErCl6.
[0141] In some embodiments, the polymer solid electrolyte includes, but is not limited to, at least one of polyacrylic acid, polyoxyethylene, polyacrylonitrile, polymethyl methacrylate, polyvinylidene fluoride, and polymethyl methacrylate.
[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A method for producing an all-solid battery, characterized by, The method comprises the following steps: S1, laminating: transferring the composite electrode sheet to an operation platform, placing the positive electrode sheet above the composite electrode sheet to form a laminated structure; wherein the composite electrode sheet comprises a negative electrode sheet and a solid-state electrolyte layer arranged on the two side surfaces of the negative electrode sheet; S2, first gluing: gluing the tab area of the positive electrode sheet to form a first glue layer; S3, second gluing: starting from the edge of the tab of the positive electrode sheet, gluing along the edge of the positive electrode sheet on the solid-state electrolyte layer, and then curing to form a second glue layer, thereby obtaining an intermediate structure; S4, laminating again: stacking the composite electrode sheet and the positive electrode sheet on the intermediate structure; Steps S2-S4 are repeated until the preset number of layers is reached, thereby obtaining a full solid-state battery.
2. The production method according to claim 1, characterized by, In step S1, the laminated structure is also pre-pressed.
3. The preparation method according to claim 1, characterized in that, In step S1, the edge alignment of the laminated structure is detected by a detection device.
4. The method of claim 1, wherein, In step S1, the active material layer area of the positive electrode sheet is fixed by a pressing plate.
5. The preparation method according to claim 1, characterized in that, In step S3, the curing method is photocuring.
6. The method of claim 1, wherein, The preparation method further comprises die cutting the edge of the intermediate structure.
7. The preparation method according to claim 1, characterized in that, The preparation method further comprises compounding the negative electrode sheet with the solid-state electrolyte layer to prepare a composite electrode sheet.
8. An apparatus for producing an all-solid battery, characterized by The preparation method is used to implement the above preparation method.
9. The preparation device according to claim 8, characterized in that The preparation device comprises an operation platform, a transfer module, and a gluing module, wherein the transfer module comprises a positive electrode sheet transfer mechanism and a composite electrode sheet transfer mechanism; The gluing module is configured to form a first glue layer and a second glue layer around the tab of the positive electrode sheet.
10. An all-solid battery, characterized by The full solid-state battery is prepared by the preparation method of claim 1 and / or by the device of claim 8.
Citation Information
Cited By
Method for assembling all-solid-state battery and all-solid-state battery
CN122267254A